Family Control and Corporate Social Responsibility: The Moderating Effect of the Board of Directors - Brahem, Emna; Depoers, Florence; Lakhal, Faten (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This paper examines the effect of family control on corporate social responsibility (CSR) in French-listed companies. Based on quantile regressions, our results show that family identity and involvement in capital and management positively influence CSR performance, particularly for low-CSR firms. These findings support the socio-emotional perspective of family firms. However, families with excess control engage less in CSR activities for expropriation purposes. Additional analysis shows that board size and gender diversity attenuate the negative effect of excess family control on CSR performance and help then mitigating the expropriation risk by family-controlled firms.